2017
DOI: 10.3791/56571
|View full text |Cite
|
Sign up to set email alerts
|

A Millimeter Scale Flexural Testing System for Measuring the Mechanical Properties of Marine Sponge Spicules

Abstract: Many load bearing biological structures (LBBSs)-such as feather rachises and spicules-are small (<1 mm) but not microscopic. Measuring the flexural behavior of these LBBSs is important for understanding the origins of their remarkable mechanical functions. We describe a protocol for performing three-point bending tests using a custom-built mechanical testing device that can measure forces ranging from 10 to 10 N and displacements ranging from 10 to 10 m. The primary advantage of this mechanical testing device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The geometrically complex siliceous skeletal systems of marine sponges have attracted a great deal of attention from the scientific community due to their multi-scale structural hierarchical organization and remarkable damage tolerance [1][2][3]. For example, the mineralized tubular skeleton from one such species, Euplectella aspergillum, consists of bundles of individual needle-like elements (spicules) that are cemented together to form a diagonally reinforced square lattice-like structure that is further covered by a series of helical ridgelike features [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometrically complex siliceous skeletal systems of marine sponges have attracted a great deal of attention from the scientific community due to their multi-scale structural hierarchical organization and remarkable damage tolerance [1][2][3]. For example, the mineralized tubular skeleton from one such species, Euplectella aspergillum, consists of bundles of individual needle-like elements (spicules) that are cemented together to form a diagonally reinforced square lattice-like structure that is further covered by a series of helical ridgelike features [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…First, single-spicule studies have revealed the presence of an underlying laminated architecture consisting of concentric lamellae of consolidated silica nanoparticles separated by thin organic interlayers. The silica layers decrease in thickness from the spicule core to its periphery, resulting in a functionally graded design that effectively retards crack propagation through the spicules, while simultaneously increasing their buckling resistance [3,6].…”
Section: Introductionmentioning
confidence: 99%